Identifikasi Parasit pada Biawak Air (Varanus salvator) - Muhammad Hanafiah; Hoky Deora Alfiansyah; Arman Sayuti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
This research has purposes to identify parasites as well as to reward determining the prevalence of parasites on water monitor lizard (Varanus salvator) was captured in Banda Aceh. As many as 50 water monitor lizard were used this research and examined at the Laboratory of Parasitology, Faculty of Veterinary Medicine University of Syiah Kuala. Examination of ectoparasites on the surface of the body was done by direct examination. Endoparasit examination carried out by observation in blood using the blood smear and centrifugation techniques microhematocrit (mHCT), while fecal examination using flotation method, Borray sedimentation and digestive tract surgery digestive tract surgery if obtained at least 3 types of helminth eggs (1 cestodes, 1 nematodes, and 1 trematodes). Results of observation on blood is no parasites were found. Observations on the skin was obtained ectoparasites Amblyomma sp. with a prevalence rate of 100% category always. Observations of feces obtained Ascaris sp. with a prevalence rate of 74% category usualy and Stronyloides spp. with a prevalence rate of 8% category sometimes. Based on these results it can be concluded that the parasites that can infest the water monitor lizard (Varanus salvator) is Amblyomma sp, Ascaris sp, and Stronyloides spp. with variant prevalence rates.